Immediate Provisionalization of a Narrow-Diameter Implant in the Mandibular Lateral Incisor Region: A Clinical Case Report - López Carriches, Carmen; Ghaffari , Hujjatullah; Taheri , Ricardo; Leco Berrocal, Isabel (Update Dental College Journal, 2025)
Introduction: We present the clinical case of a patient who had lost his right lower lateral incisor due to caries and underwent replacement with a dental implant and immediate provisionalization. Replacing a single lower incisor is clinically challenging due to limited mesiodistal space; however, aesthetic demands are somewhat reduced compared to upper incisors due to lower visibility. Methods: A 56-year-old male presented for replacement of tooth 4.2. Cone beam CT confirmed adequate bone height and width, with limited space between adjacent teeth. A 3.25 × 10 mm BT Klassic implant (Biotec, Italy) was placed following standard protocol under local anesthesia. Immediate provisionalization was achieved using a non-rotating abutment and an acetate crown. Postoperative care included antibiotics, analgesics, and chlorhexidine rinses. Results: The implant achieved good primary stability. Healing was uneventful, and sutures were removed after 7 days. Two months later, a carious lesion on tooth 4.1 was restored before final impression. A screw-cement retained crown was delivered, torqued to 20 N, and the fit was confirmed radiographically. Conclusion: This case illustrates the successful use of a narrow-diameter implant with immediate provisionalization for a lower incisor replacement, overcoming spatial limitations while achieving functional and aesthetic rehabilitation. Update Dent. Coll. j: 2025; 15(1): 43-45